White spruce (Picea glauca) densities at Brooks Range treelines, Alaska (2019-2022) - Roman Dial; Russell Wong; Colin Maher; Rebecca Hewitt; Patrick Sullivan (Arctic Data Center, 2023)
Measurements of treeline white (Picea glauca) and black (P. mariana) spruce abundance during 2019, 2020, 2021 and 2022 as sampled within n = 695 5-meter (m) radius plots (area = 78.5 square meters), each centered on a selected white spruce adult called "Focal Tree". Measurements included height of stems between 0.5 and 1.4 m tall and diameter at 1.4 m for individuals taller than 1.4 m. Those individuals taller than 1.4 m tall were also stem mapped in polar coordinates with r = distance and theta as magnetic direction from a focal center white spruce tree. The purpose of this dataset was to examine spatial variation in treeline white spruce densities and basal area across the Brooks Range and in relation to local microclimates. It also provides a baseline for future stem mapping to determine changes in abundance.